Tissue-engineered temporary wound coverings. Important options for the clinician - Ehrenreich, Michael (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Finding an ideal temporary wound dressing is challenging. Although TransCyter,built on Biobraner, offers many of the characteristics of the idealwound dressing, and may have added benefits from the delivery of extra-cellular matrix (ECM) and growth factors to the wound, the downside of high cost and less convenient storage and usage are considerable barriers to its broader adoption. The low cost and established clinical utility of Biobrane sets the bar high for new products.
Keywords: Bandages; Biological Dressings; Biološke obveze; Burns; celjenje ran; medicinski material; Obveze; Opekline; Rana, celjenje; rane; therapy; Wound Healing; zdravljenje